Concept And Implementation Of “Merdeka Belajar Kampus Merdeka” Curriculum - Raranta, Joice Ester (UNIVERSITAS PAKUAN, 2022)
The development of technology and revolution affects the development of education, if there is an industrial revolution 4.0, then education also evolves into education 4.0, meaning that education must be able to adapt to existing camps, then the birth of the MBKM policy answers concerns about the influence of technological developments on education. This study aims to determine the concept and implementation of the MBKM (Merdeka Belajar Kampus Merdeka) curriculum. This research uses a documentation method with a qualitative approach, while the research model used is the Miles and Huberman interactive analysis model by reducing the data, then presenting the data, and drawing conclusions from the data obtained. The results showed that the presence of an independent learning curriculum aims to provide opportunities for students to develop capacity, creativity, personality and develop independence in seeking and finding knowledge through reality and field dynamics such as ability requirements, social interaction, cooperation, self-management, work demands, targets and their application. The implementation of the MBKM curriculum to answer the challenges of technological development, with OBE (Outcame Based Education) based learning system education so that graduates focus on learning outcomes that are in harmony with the discipline